Feasibility, Efficacy, and Safety of Radiofrequency Ablation of Atrial Fibrillation Guided by Monitoring of the Initial Impedance Decrease as a Surrogate of Catheter Contact. (20th February 2015) - REICHLIN, TOBIAS; LANE, CHRISTOPHER; NAGASHIMA, KOICHI; NOF, EYAL; CHOPRA, NAGESH; NG, JUSTIN; BARBHAIYA, CHIRAG; TADROS, TOMAS; JOHN, ROY M.; STEVENSON, WILLIAM G.; MICHAUD, GREGORY F.
AF Ablation Guided by Initial Impedance Drop Background The initial impedance decrease during radiofrequency (RF) ablation is an indirect marker of catheter contact and lesion formation. We aimed to assess feasibility, efficacy, and safety of an ablation approach guided by initial impedance decrease. Methods A total of 25 patients with paroxysmal AF had point‐by‐point, wide antral pulmonary vein (PV) isolation. RF applications were aborted if a decrease of at least 5 Ω did not occur in the first 10 seconds; otherwise, ablation was continued for at least 20 seconds. Power was 30 Watts and reduced to 15–25 Watts on the posterior wall. Results A total of 28% of RF applications were terminated because of inadequate impedance decrease. The remaining lesions showed a median decrease of 7.6 Ω (IQR 5.0–10.7) at 10 seconds and median duration of RF lesions was 38 seconds. Note that, 100 PVs were isolated with 49 rings. PVI occurred before anatomic completion of the ablation ring of adequate lesions in 39/49 (80%) and concurrent with ring completion in 7/49 (14%). Additional lesions were required in 3/49 (6%) rings. After PVI, additional lesions were required to eliminate dormant conduction in 2/47 (4%) and pace‐capture on the ablation line in 24/49 vein pairs (49%). During short‐term follow‐up, 3 nonfatal esophageal injuries and 2 late pericardial effusions occurred. During a mean follow‐up of 431 ± 87 days, 21/25 patients (84%) remained free of recurrent symptomatic atrial arrhythmias. Conclusions PVI guided by initial impedance decrease is feasible and results in PVI concurrent with or before completion of the ablation ring in 94% of patients. Single procedure efficacy after one year of follow‐up was 84%. Near‐term complications suggest that deeper lesions are created, indicating that further reduction of RF‐power and duration is warranted.